Empirical Evaluation of Understandability and Usability of Health Handbooks Commonly Used in Japan - Nomura, Marika; Goto, Aya; Osawa, Eri; Miura, Hiroko (Frontiers in Communication, 2021)
Objective: Various types of handbooks that summarize and record health information (health handbooks) have been used in Japan for many years. The purpose of this study was to explore ways to evaluate the understandability and usability of commonly used printed health handbooks in Japan. Methods: An internet search was performed to identify health handbooks used in Japan. The handbooks were then collected, searched, and evaluated for the quality and functionality of the health-information. The overall understandability was assessed using the Suitability Assessment of Material (SAM) and the Centers for Disease Control and Prevention Clear Communication Index (CCI), and overall usability was assessed using a purpose-user matrix. Results: A total of 14 health handbooks were extracted and analyzed. The median scores for SAM and CCI were 39 (min 25, max 45) and 81.5% (60%, 100%), respectively, and no significant association was observed between the two evaluation scores. Based on the matrix, the most common type of handbook was those designed for preventive purposes that the user or their family completed (n=9). Conclusion: Our sampled health handbooks were used mostly for preventive purposes and their understandability varied. SAM and CCI assess different aspects of written materials and it is recommended they be used together when evaluating the understandability of health handbooks. To facilitate more effective use of health handbooks in public health activities, we suggest the content of handbooks be assessed by a purpose-user matrix.